2009
DOI: 10.1146/annurev.pathol.4.110807.092246
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Cancer

Abstract: Ovarian carcinomas are a heterogeneous group of neoplasms traditionally sub-classified based on type and degree of differentiation. Although current clinical management of ovarian carcinoma largely fails to take this heterogeneity into account, it is becoming evident that each major histological type has characteristic genetic defects that deregulate specific signaling pathways in the tumor cells. Moreover, within the most common histological types, the molecular pathogenesis of low-grade versus high-grade tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
615
0
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 642 publications
(639 citation statements)
references
References 128 publications
15
615
0
9
Order By: Relevance
“…[9][10][11][12] The classification of ovarian epithelial tumors currently used by pathologists is based entirely on tumor cell morphology, architectural pattern, nuclear atypia and stromal invasion. 8,13,14 The cell type may be serous, mucinous, endometroid, Brenner/transitional, clear cell and undifferentiated. These cell types bear strong resemblance to the normal cell lining of different organs in the female genital tract.…”
Section: Peritoneal Implant 11mentioning
confidence: 99%
“…[9][10][11][12] The classification of ovarian epithelial tumors currently used by pathologists is based entirely on tumor cell morphology, architectural pattern, nuclear atypia and stromal invasion. 8,13,14 The cell type may be serous, mucinous, endometroid, Brenner/transitional, clear cell and undifferentiated. These cell types bear strong resemblance to the normal cell lining of different organs in the female genital tract.…”
Section: Peritoneal Implant 11mentioning
confidence: 99%
“…A number of studies have demonstrated that the halflife of mutated p53 (several hours) is markedly increased compared to wild-type (several minutes) which may result in its accumulation in the cell nucleus and the accumulation of protein rather than the mutations has been suggested as the immunogenic trigger that results in autoantibody generation [17]. Clinicopathological and molecular studies suggest that ovarian carcinoma can be divided in two broad categories, "Type I" and "Type II" tumors [8]. The terms, "Type I" and "Type II"…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Ovarian cancer when diagnosed in early stages results in over 90% 5-year survival rate, however if diagnosed in late stage this drops to only 30% 5-year survival rate [8].…”
Section: Introductionmentioning
confidence: 99%
“…
Dear Editor: Ovarian carcinoma is the most lethal gynecological cancer [1], and the endometrioid type accounts for 7-20 % of all cases [2]. The gastrointestinal stromal tumor (GIST) may mimic ovarian tumors, as reported previously by other authors [3,4].
…”
mentioning
confidence: 98%